Short-term effects of COVID-19 on income distribution in Colombia’s five major cities - Alonso Cifuentes, Julio César; Chavarriaga Antonio, Viviana (Sociedad y Economía, 2025)
We analyzed changes in household income distribution across the five major Colombian cities from 2018 to 2021 using micro data from GEIH and the nonparametric Relative Distribution Method (RDM). We examine the relative income distributions and polarization indices for four intervals: 2018-2019, 2019-2020, 2020-2021, and 2018-2021. Results show that in Bogota, Medellin, Cali, and Barranquilla, household income polarization increased in 2018-2019, decreased in 2019-2020, and increased again for 2020-2021. In Medellin, in all periods, there was income polarization. In the first period, Bucaramanga exhibits a reduction in polarization and, in the other periods, an increase. For the whole period (2018-2021) in Bucaramanga, Medellin, Cali, and Bogota, polarization and Barranquilla polarization decreased. This study contributes to the literature in at least two aspects. For the first time, it employs the MDR to study changes in income distributions at the municipal level. And second, it generates evidence of what happened with the distribution of household income during the pandemic period.